High Glucose Induced Changes in Human VEC Phenotype in a 3D Hydrogel Derived From Cell-Free Native Aortic Root - Cecoltan, Sergiu; Ciortan, Letitia; Macarie, Razvan D.; Vadana, Mihaela; Mihaila, Andreea C.; Tucureanu, Monica; Vlad, Mihaela-Loredana; Droc, Ionel; Gherghiceanu, Mihaela; Simionescu, Agneta; Simionescu, Dan Teodor; Butoi, Elena; et al. (Frontiers in Cardiovascular Medicine, 2021)
Background: Valvular endothelial cells (VEC) have key roles in maintaining valvular integrity and homeostasis, and dysfunctional VEC are the initiators and major contributors to aortic valve disease in diabetes. Previous studies have shown that HG stimulated an inflammatory phenotype in VEC. Inflammation was shown to induce endothelial to mesenchymal transition (EndMT), a process extensively involved in many pathologies, including calcification of the aortic valve. However, the effect of HG on EndMT in VEC is not known. In addition, there is evidence that endothelin (ET) is a proinflammatory agent in early diabetes and was detected in aortic stenosis, but it is not known whether HG induces ET and endothelin receptors and whether endothelin modulates HG-dependent inflammation in VEC. This study aims to evaluate HG effects on EndMT, on endothelin and endothelin receptors induction in VEC and their role in HG induced VEC inflammation. Methods and Results: we developed a new 3D model of the aortic valve consisting of a hydrogel derived from a decellularized extracellular cell matrix obtained from porcine aortic root and human valvular cells. VEC were cultured on the hydrogel surface and VIC within the hydrogel, and the resulted 3D construct was exposed to high glucose (HG) conditions. VEC from the 3D construct exposed to HG exhibited: attenuated intercellular junctions and an abundance of intermediate filaments (ultrastructural analysis), decreased expression of endothelial markers CD31 and VE–cadherin and increased expression of the mesenchymal markers α-SMA and vimentin (qPCR and immunocytochemistry), increased expression of inflammatory molecules ET-1 and its receptors ET-A and ET-B, ICAM-1, VCAM-1 (qPCR and Immunocytochemistry) and augmented adhesiveness. Blockade of ET-1 receptors, ET-A and ET-B reduced secretion of inflammatory biomarkers IL-1β and MCP-1 (ELISA assay). Conclusions: This study demonstrates that HG induces EndMT in VEC and indicates endothelin as a possible target to reduce HG-induced inflammation in VEC.